Effect of Moisture on Mechanical Properties and Thermal Stability of Meta-Aramid Fiber Used in Insulating Paper - Yin, Fei (Polymers (Basel), 2017)
Seven composite models of meta-aramid fibers with different moisture contents were studied using molecular dynamics simulation. The effects of moisture on the thermal stability and mechanical properties of the fibers and their mechanisms were analyzed, considering characteristics such as hydrogen bonding, free volume, mean square displacement, and mechanical parameters. The simulation results showed that the large number of hydrogen bonds between water molecules and meta-aramid fibers destroyed the original hydrogen-bond network. Hydrogen bonds between the molecular chains of meta-aramid fibers were first destroyed, and their number decreased with increasing moisture content. The free volume of the fibers thereby increased, the interactions between fiber chains weakened with increasing moisture content, and the fiber chain movement intensified accordingly. The ratio of diffusion coefficients of the water molecules to moisture contents of the composite models increased linearly, and the water molecule diffusion increased, which accelerated the rate of damage to the original hydrogen-bond network of the meta-aramid fibers and further reduced their thermal stability. In general, the mechanical properties of the composites were negatively related to their moisture content.